Maintenance Task Allocation And Planning In KT. X Tugboat Using Reliability Centered Maintenance Method - Dwi Priyanta; Muhammad Badrus Zaman; Apriagung Diantana P (International Journal of Marine Engineering Innovation and Research, 2017)
Reliability Centered Maintenance (RCM) as one of the processes that used to decisive action which should be performed to ensure any physical components or a system can work optimally in accordance with the function desired by its users. Basically, RCM used a risk management principles of the failure of the components so that it can be determined the type of maintenance properly. With the appropriate type of maintenance, then the failures that may occur can be prevented at once to be able to be detected before they occur. Appropriate implementation of RCM, capable of delivering cost savings, the impact on both the cost of maintenance as well as repair costs due to the occurrence of failure. In this paper, the components become the object of research is the main engine of the KT. X tugboat belongs to Pelindo Marine Service (PMS) Surabaya. KT. X tugboat has the lowest level of availability of the entire company-owned tugboat 80.01 percent. Tugboat is one of the main assets of PMS who support the economy of the company. Therefore, it is imperative for a company to further enhance the efficiency of activities of its operations. These include the efficiency of human resources, as well as economic analysis of system reliability of company assets. It is used in order to keep abreast of competition at the world maritime national and globally. Implementation of RCM process on main engine KT. X, priority levels can be specified against the failure of components that have critical consequences. So it can be a planned maintenance system generated properly and efficiently.